2017
DOI: 10.1159/000479430
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Infection with <b><i>Plasmodium vivax</i></b> and the Dengue and Chikungunya Viruses in a Paediatric Patient from New Delhi, India in 2016

Abstract: Dengue and chikungunya fevers are transmitted by the common mosquito vector Aedes and malaria by Anopheles. Concurrent infections are reported due to co-circulation of these pathogens, especially in endemic regions. We report a rare case of triple infection with 3 arthropod-borne pathogens (Plasmodium vivax and the dengue and chikungunya viruses) in a 3-year-old child from New Delhi, India, in August 2016. The viruses were identified by RT-PCR and the parasite by microscopy and antigen detection. The dengue vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…An investigation reported concurrent infection with Plasmodium, DENV and CHIKV in a traveler from India [14]. Other reports also showed mixed infection with three pathogens from India [15]. The present study describes such case of mixed infection with three pathogens transmitted by mosquitoes from New Delhi, India during monsoon season 2016.…”
supporting
confidence: 53%
“…An investigation reported concurrent infection with Plasmodium, DENV and CHIKV in a traveler from India [14]. Other reports also showed mixed infection with three pathogens from India [15]. The present study describes such case of mixed infection with three pathogens transmitted by mosquitoes from New Delhi, India during monsoon season 2016.…”
supporting
confidence: 53%
“…1). Two samples showed concurrent infection by three arthropod mediated pathogens, namely, DENV-3, CHIKV and Plasmodium vivax [27, 28].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…References/sources for these reports are given in Supplementary Table S2 and S3. Another interesting aspect of the investigation was concurrent infection with three different arthropod mediated pathogens (DENV, CHIKV and Plasmodium vivax ) in two patients [27, 28]. Such cases of infection with multiple pathogens pose a challenge for the diagnosis of the aetiological agents due to the overlapping clinical spectrum of the three diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have reported co‐infections of CHIKV with pathogens such as Zika virus (ZIKV), dengue virus (DENV), and malaria parasites in humans although the pathological outcomes of these co‐infections have not been clearly defined. Particularly, different clinical reports from African malaria cohorts suggested the presence of CHIKV infections. Furthermore, the highly pro‐inflammatory profiles of both diseases—including the detrimental contribution of T cell‐mediated immune responses to the pathologies—and the immunosuppressive nature of malaria infections speculate that immune modulation might occur.…”
Section: Co‐infection With Plasmodium Parasites Modulates Chikv Pathomentioning
confidence: 99%